Waste Policy Management in the Bengawan Solo River Basin in the Surakarta Area, Indonesia - Absori, Absori; Budiono, Arief; Rizka, Rizka; Hernanda, Trias; Bangsawan, Moh Indra; Achmadi, Achmadi (Faculty of Law, Universitas Pekalongan, 2025)
Introduction: The waste management in the Bengawan Solo River basin in Indonesia leaves a feeling of profound sadness as the river is filled with waste and is very dirty. It decreases the quality of the river water and the environment around the river basin. This research aims to analyze the implementation of waste management around the Bengawan Solo River basin. This was a type of sociological legal research, i.e., research which utilized data from the field. This was descriptive qualitative research, meaning that it describes the policy on waste management in the Bengawan Solo River basin and the authors selected qualitative data to be analyzed. The authors conducted the sociological approach which was obtained from respondents through interviews and observation in the field. The data were processed and analyzed qualitatively. Then, the authors drew a conclusion. Results and Discussion: There is a very high volume of pollution and waste in the Bengawan Solo River as society lacks environmental awareness, making them not think twice about littering in rivers. Apart from that, the government does not carry out enough systematic efforts by educating society, implementing legal sanctions, or cleaning the river, worsening the condition of this river. Conclusion: The government needs to show a firm attitude in law enforcement by imposing sanctions on pollution and littering perpetrators in the Bengawan Solo River as well as increasing the budget and apparatus to carry out river cleaning activities.